Effort thrombosis of the upper extremity in a young sportsman: Paget–Schroetter syndrome. Issue 8 (8th February 2007) - Roche-Nagle, Graham; Ryan, Ronan; Barry, Mary; Brophy, David
Abstract : Paget-Schroetter syndrome is the spontaneous thrombosis of the axillary/subclavian vein. A 16-year-old male presented with acute onset of right upper limb swelling after vigorous weight training. A venogram confirmed the diagnosis of Paget–Schroetter syndrome. He was started on intravenous thrombolytics followed by oral anticoagulation therapy. His symptoms resolved and he was symptom free at six-month follow-up. Thrombolytics and anticoagulation is the most widely accepted first-line therapy for this syndrome. Defining any anatomical anomaly as the predisposing factor in this condition is essential in the selection of which patients will benefit from thoracic outlet decompression.